2019
DOI: 10.4103/sja.sja_799_18
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of low-dose bupivacaine spinal anesthesia for cesarean section: A randomized controlled trial

Abstract: Background: Spinal anesthesia is the most common technique for cesarean section. The conventional local anesthetic dose has been decreasing over time to 8–12.5 mg of bupivacaine. Lower doses of bupivacaine may be associated with reduced incidence of hypotension and other complications. This low dose also may be associated with improved maternal cardiac index (CI). We hypothesized that low dose spinal anesthesia using 4.5 mg bupivacaine would result in improved maternal CI when compared with conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The total amounts of ephedrine and noradrenaline were comparable in both groups of our study, as reported by some earlier studies. 31,32 Ben-David et al, however, found a significant decline of the total amount of the vasopressor ephedrine in geriatric patients who received 4 mg bupivacaine added to fentanyl compared to 10 mg bupivacaine only in hip operations. 33 The incompatible findings might be due to the great difference between the two used doses of bupivacaine (10 vs. 4 mg) by them, while we used 12.5 vs. 9.79 mg of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The total amounts of ephedrine and noradrenaline were comparable in both groups of our study, as reported by some earlier studies. 31,32 Ben-David et al, however, found a significant decline of the total amount of the vasopressor ephedrine in geriatric patients who received 4 mg bupivacaine added to fentanyl compared to 10 mg bupivacaine only in hip operations. 33 The incompatible findings might be due to the great difference between the two used doses of bupivacaine (10 vs. 4 mg) by them, while we used 12.5 vs. 9.79 mg of bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ischemic heart disease and cardiomyopathy have increased sympathetic activity to maintain the cardiac output, and so are at increased risk of decrease in SVR with high dose spinal anaesthesia [8]. Cenkowski JM 2019 et al showed that low-dose bupivicaine group gain faster recovery of the sensory and motor blockade, early discharge, and better patient satisfaction compared to high dose bupivacaine [9]. Alsaeid et al also found that a small dose of heavy bupivacaine 0.5% (5 mg) provided better hemodynamic stability with minimal side effects in elderly patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian ini didapatkan rata-rata durasi prosedur pembedahan 1: 12 Hasil ini berbeda dengan penelitian pada populasi Indonesia yang membandingkan anestesi spinal low dose pada seksio sesarea menggunakan bupivakain hiperbarik 0,5% 7,5 mg dengan 5 mg dengan 56 subjek pada masing-masing kelompok. Penelitian ini menggunakan adjuvan tunggal (fentanil 25mcg) pada kedua kelompok.…”
Section: Pembahasanunclassified
“…16 Selain itu posisi pasien saat obat lokal anestesi diinjeksi juga memengaruhi anestesi spinal, pada suatu penelitian membandingkan kelompok low dose dan conventional dose dengan kedua kelompok dalam posisi duduk, 7 sementara pada penelitian lain posisi duduk pada kelompok conventional dose sedangkan kelompok low dose dengan posisi miring ke kanan dan Trendelenberg 10 o . 12 Dari suatu meta-analisis yang terdiri dari 12 penelitian dengan total 693 pasien yang membandinglan kejadian suplementasi analgesia intraoperatif pada seksio sesarea antara kelompok low dose (≤ 8 mg ) vs bupivakain conventional dose (>8mg). Dosis bupivakain yang digunakan pada 12 penelitian ini beragam antara 4-12,5mg.…”
Section: Pembahasanunclassified